Functional and cognitive profile of elderly residents in a long‑term care institution in the northeast - Santos, Adryanne Almeida; Silva, Ana Lídia Santos Barros da; Santos, Felipe Arllan Bezerra; Barbosa, Juliana Eletícia Silva; Almeida, Laize Pacheco Dos Santos; Mota, Renata de Sousa; Santos, Alan Carlos Nery dos (Manual Therapy, Posturology & Rehabilitation Journal, 2019)
Background: Aging is a physiological process characterized as the beginning of a stage of life in which happen social, physical and psychological changes. Among these, cognitive and functional decline has been one of the most frequent, and may be enhanced by the process of institutionalization. Objectives: The aim of this study was to describe the cognitive and functional profile of elderly residents in a Long-Term Care Institution for the Elderly (LTCI). Methods: A cross-sectional descriptive study whose population was composed of elderly people of both genders, residents in the “Associação Feirense de Assistência Social” in Feira de Santana (BA), Brazil. The elderly with physical and mental limitations that made it impossible to perform the functional and cognitive tests were excluded from the study. The survey was completed in December 2017. The Barthel Index, Katz Index, Berg Balance Scale (BERG) and Timed Up and Go (TUG) were used for functional evaluation. The first two tools were used to classify functional independence in the activities of daily living (ADL’s), and the others to categorize risk of fall. It was used the Mini-Mental State Exam to evaluate cognition. In addition, a form was created to collect clinical and sociodemographic variables. The results of this study were described in percentage. Results: From the 35 elderly residents, 25 were included, of which 15 were female, with ages between 62 and 95 years. Regarding Education, 60% are illiterate, 32% have 1 to 4 years, 4% have 5 to 8 years and 4% have 9 to 11 years of studies. 92% of the population presented cognitive alterations. Regarding functionality, 66.6% of the elderly had a dependent gait, with 56.2% of females. In the assessment of the risk of falling, 60% presented moderate risk by TUG and 82.6% presented a high risk by the Berg scale. Considering the Barthel index and the Katz index, 52% had dependence on ADLs. 96% did not practice physical activity and 62.5% did not undergo Physical Therapy. The most frequent comorbidities were arterial hypertension (64.3%) and diabetes mellitus (36%). Conclusion: The results of this study indicate that the studied population presents cognitive alterations, gait dependent, greater probability for risk of falls, low level of education and physical activity, besides longevity, which may suggest that the institutionalization process brings negative repercussions for these subjects.